Case study about modernizing electronic data interchange (EDI) order system - Saarinen, Antti (fi=Turun yliopisto|en=University of Turku|, 2018)
Electronic data interchange (EDI) messages are an old format of changing electronic forms between companies. Even though more modern message standards like XML exists, many organizations still use EDI to place orders and receive invoices in their business practices. In this kind of system, it is hard to implement new features. This thesis presents methods used to modernize legacy systems. Three different methods are presented and overview of them is given. History of EDI and its message structure is presented as well as modern alternatives to replace it. Comparison between EDI and XML is presented. In this thesis an EDI powered order system of a logistic company is examined. Documentation work to understand different EDIFACT messages is performed. With this new understanding of the order system, a Renaissance modernization method is used to come up with different modernization options for this system. It can be observed that legacy systems are still widely used in business to business communication. With many partners still using EDI, it is difficult to make interface changes to such business-critical system.